2001
DOI: 10.1136/gut.48.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor reduces multiorgan failure induced by thioacetamide

Abstract: Background-Multiorgan failure is a severe life threatening state where present therapeutic approaches are suboptimal. Epidermal growth factor (EGF) is a potent stimulant of repair in in vitro and in vivo models. We therefore examined its potential beneficial eVect in reducing mortality and injury induced by the noxious agent thioacetamide (TAA). Methods-Mice (20 per group) were fasted overnight and received a single intraperitoneal dose of human recombinant EGF at 10 or 30 µg/kg or saline (control). Either 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…This is in contrast to the heart or gastric mucosa in which EGF protects against acute stressinduced injury (11,42). However, a lack of liver protection by exogenous EGF administration was also described by Caballero et al (14) in a model of thioacetamide-induced multiorgan failure. These authors observed however, that exogenous EGF did protect the small intestine and kidneys.…”
Section: Discussionmentioning
confidence: 89%
“…This is in contrast to the heart or gastric mucosa in which EGF protects against acute stressinduced injury (11,42). However, a lack of liver protection by exogenous EGF administration was also described by Caballero et al (14) in a model of thioacetamide-induced multiorgan failure. These authors observed however, that exogenous EGF did protect the small intestine and kidneys.…”
Section: Discussionmentioning
confidence: 89%
“…Light microscopic examination of the renal tissue found only minor degenerative acute alterations in the proximal tubules but without significant signs of tubular necrosis or loss of tubule patency, results generally in agreement with previous observations. 31,32 Renal function assessment also revealed no significant changes in fractional sodium excretion or free water and osmolar clearance in rats that received TAA, indicating the renal tubules retained the ability to concentrate urine. These results suggest that the decreased urine production observed in rats that received TAA in the present study was not likely to have been caused by the direct toxic effects of TAA on renal tissue but was related mainly to the alteration in renal function from the decrease in the GFR and the increased tubular reabsorption of water and sodium.…”
Section: Discussionmentioning
confidence: 93%
“…There are however a number of serious gastrointestinal pathologies where novel therapies might prove useful, including their use for multiorgan failure, 4 necrotising enterocolitis, 5 and liver protection and regeneration. 6 Three conditions worthy of particular focus are short bowel syndrome, chemotherapy induced mucositis, and inflammatory bowel disease. These are discussed further below.…”
Section: Growth Factor Agonistsmentioning
confidence: 99%